2007
DOI: 10.1002/adma.200601774
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of a Dipeptide‐ Containing Conformationally Restricted Dehydrophenylalanine Residue to Form Ordered Nanotubes

Abstract: The self‐assembly of a dehydrophenylalanine containing dipeptide (see figure), yielding highly ordered nanotubular structures, is discussed. The tubes are longer and thinner than previously reported peptide‐based tubular structures; they are stable to boiling‐water temperatures, different pH conditions, and to a highly nonspecific protease (Proteinase K).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
155
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(172 citation statements)
references
References 32 publications
15
155
0
2
Order By: Relevance
“…conformation. 65,66 In all cases these structural characteristics are preserved between -50 ºC and +60 ºC, as is demonstrated by the spectra acquired at different temperatures within such interval ( Figure S3). …”
Section: Structure Of the Sheets And Intermolecular Interactionssupporting
confidence: 59%
“…conformation. 65,66 In all cases these structural characteristics are preserved between -50 ºC and +60 ºC, as is demonstrated by the spectra acquired at different temperatures within such interval ( Figure S3). …”
Section: Structure Of the Sheets And Intermolecular Interactionssupporting
confidence: 59%
“…[22][23][24][25][26][27] Several reports, including our own studies, have shown that dipeptides, either free or with N-or C-terminal modifications, can self-assemble into well-defined NPs. 18,19,[28][29][30] However, most of these studies have shown assembly in an aqueous environment and may not be suitable for delivering hydrophobic bioactive molecules. Thus, we attempted to develop dipeptide-based nanostructures, which can be prepared in organic or aqueous-organic environments, for potential loading of hydrophobic drugs.…”
Section: Results and Discussion Preparation And Characterization Of Npsmentioning
confidence: 99%
“…19,29 Although this solvent is excellent for dissolving peptides, it may not be suitable if the self-assembled structures are to be developed for in vivo studies due to high toxicity. 31 Therefore, we sought to replace HFIP with a more suitable solvent.…”
Section: Results and Discussion Preparation And Characterization Of Npsmentioning
confidence: 99%
See 2 more Smart Citations